A novel mutation (Q40P) in PAX8 associated with congenital hypothyroidism and thyroid hypoplasia: Evidence for phenotypic variability in mother and child - Congdon, Tamara; Nguyen, Lynda Q.; Nogueira, Celia R. [UNESP]; Habiby, Reema L.; Medeiros-Neto, Geraldo; Kopp, Peter (The Endocrine Society, 2001)
Congenital hypothyroidism associated with thyroid hypoplasia can be caused by several genetic defects, including mutations in the TSHβ-subunit, the TSH receptor, the Gsα-subunit, and the transcription factor PAX8. Four girls with sporadic congenital hypothyroidism and hypoplastic thyroid glands were analyzed for mutations in PAX8 and TTF2 (FKHL15). Mutations in the coding region of the TSHβ-subunit gene, the TSH receptor gene, and exons 8 and 9 of Gsα had been excluded previously. Serum TSH concentrations were 150 mU/liter or more, TG levels were within normal limits, and thyroid auto-antibodies were absent. Technetium scintigraphies did not reveal the presence of thyroid tissue, but ultrasonography documented hypoplastic, normally located glands. One patient was found to harbor a heterozygous transversion 119A→C in exon 3 of PAX8 replacing a conserved glutamine by proline in the paired box domain (Q40P). Analysis of her family members revealed that her mother, who has a thyroid gland of normal size and mild, adult-onset autoimmune hypothyroidism, is also heterozygous for this mutation. Functional analyses of the PAX8 Q40P mutation showed impaired binding to a PAX8 response element and absent transactivation of a thyroid peroxidase promoter luciferase reporter gene. These findings confirm the important role of PAX8 in the development of the thyroid, but they indicate that PAX8 gene mutations may have a variable penetrance or expressivity. The absence of mutations in the coding sequences of the analyzed genes in the three other patients supports the concept that the pathogenesis of congenital hypothyroidism associated with thyroid hypoplasia is diverse.